Dampak Pajak Penambangan dan Galian Mineral Bukan Logam Batuan (MBLB) terhadap Pendapatan Asli Daerah Kabupaten Lombok Timur - Yuniati, Musniasih; Salkiah, Baiq; Yorman, Yorman; Silviana, Firda (YASIN, 2024)
This study aims to determine the Impact of Non-Metal Rock Mineral Mining and Excavation Tax (MBLB) on the Original Regional Income of East Lombok Regency. The research method used is a quantitative method with an inferential approach. The data used is a type of secondary Time Series data in the form of Non-Metal Rock Mineral Tax (Galian Mineral Bukan Logam Batuan, MBLB) data and Original Regional Income data for East Lombok Regency in 2019-2023. The results of the study indicate that there is an impact of Non-Metal Rock Mineral Tax on the Original Regional Income of East Lombok Regency by 10 percent. The implication of this study is the importance of increasing Original Regional Income through other sectors that have great potential to be developed.